Transimpedance Amplifier for Short-Reach SI-POF Links - Royo, Guillermo; Gimeno, Cecilia; Sánchez-Azqueta, Carlos; Aldea, Concepción; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2023)
This paper presents the design of a low-power lowvoltage transimpedance amplifier for short reach applications through low-cost step index plastic optical fiber. The amplifier has been designed in a 180 nm CMOS technology and dissipates 6 mW from a supply voltage of only 1 V. The design achieves 1.25 Gb/s through 50 m POF and a sensitivity of -20 dBm considering a 10-12 BER.